Transformation and Summation Formulas for Exton's Functions K11, K14 And K15 - Ahmed Ali Atash; Hussein Saleh Bellehaj (مجلّة جامعة عدن للعلوم الأساسيّة والتّطبيقيّة, 2020)
The aim of the present paper is to establish some transformation formulas for Exton's quadruple hypergeometric functions K11, K14 and K15. Several summation formulas for K11, K14 and K15 are also derived as an applications of our main results with the help of classical summation theorems.